Penerapan Project-Based Learning untuk Meningkatkan Kesadaran Lingkungan Siswa SDN Kabuaran 01 Bondowoso - Aulfatur Raudah; Hoirus Soleh; Muhammad Wayan Suphan Putra; Revalina Jasmine; Farah Zayyana Aqilah; Luna Oktafianti Ramadhani; Septiana Dewi Putri Rosifah; Agung Nugroho Puspito; Dinawati Trapsilasiwi (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program aims to increase environmental awareness among students at SDN Kabuaran 01 Bondowoso through a participatory approach and Project-Based Learning (PjBL). The activity was carried out for three weeks, involving students in grades I–VI in waste management, recycling practices, and school greening. Evaluation results showed a significant increase in student understanding. The average pre-test and post-test scores for waste management and recycling increased from 60% to 89%, while for greening increased from 61% to 92%. In addition to improving cognitive aspects, student participation and active involvement in practical activities also increased. These findings indicate that the implementation of PjBL is effective in developing environmental awareness and behavior in elementary school students. Therefore, similar programs are recommended to be integrated into school learning and extracurricular activities on an ongoing basis.